Comparison of lung ultrasound, chest radiographs, C‐reactive protein, and clinical findings in dogs treated for aspiration pneumonia - Nina Fernandes Rodrigues; Léna Giraud; Géraldine Bolen; Aline Fastrès; Cécile Clercx; Søren Boysen; Frédéric Billen; Kris Gommeren (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Comparison of clinical findings, chest radiographs (CXR), lung ultrasound (LUS) findings, and C‐reactive protein (CRP) concentrations at admission and serial follow‐up in dogs with aspiration pneumonia (AP) is lacking. Hypothesis Lung ultrasound lesions in dogs with AP are similar to those described in humans with community‐acquired pneumonia (comAP); the severity of CXR and LUS lesions are similar; normalization of CRP concentration precedes resolution of imaging abnormalities and more closely reflects the clinical improvement of dogs. Animals Seventeen dogs with AP. Methods Prospective observational study. Clinical examination, CXR, LUS, and CRP measurements performed at admission (n = 17), 2 weeks (n = 13), and 1 month after diagnosis (n = 6). All dogs received antimicrobial therapy. Lung ultrasound and CXR canine aspiration scoring systems used to compare abnormalities. Results B‐lines and shred signs with or without bronchograms were identified on LUS in 14 of 17 and 16 of 17, at admission. Chest radiographs and LUS scores differed significantly using both canine AP scoring systems at each time point (18 regions per dog, P < .001). Clinical and CRP normalization occurred in all dogs during follow up. Shred signs disappeared on LUS in all but 1 of 6 dogs at 1 month follow‐up, while B‐lines and CXR abnormalities persisted in 4 of 6 and all dogs, respectively. Conclusion and Clinical Importance Lung ultrasound findings resemble those of humans with comAP and differ from CXR findings. Shred signs and high CRP concentrations better reflect clinical findings during serial evaluation of dogs.